2012
DOI: 10.5465/amj.2010.0651
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Work Practices: A Source of Career Premiums or Penalties?

Abstract: The present research builds theory regarding how use of flexible work practices (FWPs) affects employees' career success. We integrate theory on signaling and attributions and propose that managers interpret employees' use of FWPs as a signal of high or low organizational commitment, depending on whether managers make productivity or personal life attributions, respectively, for employees' FWP use. Managers' perceptions of employees' commitment, in turn, shape employees' career success. Field-and laboratory-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
313
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(358 citation statements)
references
References 70 publications
(101 reference statements)
16
313
0
10
Order By: Relevance
“…Using field-and laboratory-based analyses for the US, another study shows that familyfriendly workplace systems (including flextime and working from home) are associated with career premiums when managers interpret the employees' choice of family-friendly workplace systems as a signal of high organizational commitment [10]. In that case, managers attribute the interest in family-friendly workplace systems to an employee's desire to increase productivity.…”
Section: Working-time Autonomy and Family-friendly Workplace Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using field-and laboratory-based analyses for the US, another study shows that familyfriendly workplace systems (including flextime and working from home) are associated with career premiums when managers interpret the employees' choice of family-friendly workplace systems as a signal of high organizational commitment [10]. In that case, managers attribute the interest in family-friendly workplace systems to an employee's desire to increase productivity.…”
Section: Working-time Autonomy and Family-friendly Workplace Practicesmentioning
confidence: 99%
“…Finally, a common feature of the empirical studies discussed in this paper is the noticeable effort devoted to identifying causal effects, whether through randomized field or laboratory experiments [4], [7], [8], [10], or through analyses of representative, large-scale survey data [2], [3], [6], [11]. Experimental studies are beneficial, because randomization excludes potential selection biases.…”
Section: Limitations and Gapsmentioning
confidence: 99%
“…In fact, research has shown that the attributions supervisors make are predictive of how well use of flexibility arrangements contributes to employee commitment and career success (Leslie et al, 2012). In their study, Leslie and colleagues (2012) found that when managers attributed flexibility use of their subordinates to productivity motives (i.e., employees use flexibility to become more productive and efficient), rather than personal life motives (i.e., employees use flexibility to accommodate nonwork activities), employees were perceived to be more highly committed to the organization, and hence achieved more career success.…”
Section: Factors Influencing the Impact Of Flexibilitymentioning
confidence: 99%
“…However, flexibility may also be related to lower dedication to one's career, and attributions by others that one is not committed to the organization (Leslie, Manchester, Park, & Mehng, 2012;Rogier & Padgett, 2004). Hence, this shows the inherent contrast that may arise from flexibility arrangements between the employee, who is able to obtain more flexibility, and the employer, who questions the employees' commitment to the organization when flexibility is perceived to be negotiated to obtain a better work-life balance.…”
Section: Theories and Models Of Workplace Flexibilitymentioning
confidence: 99%
“…In addition, based on the literature and managerial practices, we construct and examine two specific dimensions of work-family balance practices through data analysis. These are workplace flexibility, which focuses on providing flexibility at work and enhancing job autonomy, such as telecommuting, workplace flexibility, job autonomy (Leslie et al, 2012;Kossek et al 2006;Shockley and Allen, 2007;Kahn et al, 1964, p. 19), and employee and family wellness care, that involves the economic and material resources of an employee and their family-such as insurance and allowances-that compensate employees for their devotion to their work and the reduced time they spend with their family (Staines, 1980;Rothbard, 2001), thus preventing resource depletion (Premeaux et al 2007). Based on these two dimensions, we examined their differential relationships with work-family conflict, which contributes to a configurational perspective to elaborate the in-depth structures of work-family balance practices.…”
Section: Introductionmentioning
confidence: 99%